Time of symptoms to health-seeking among cervical cancer patients in Ibadan, Nigeria (2016)
Background: Early cervical cancer presentation has an excellent prognosis following treatment. Unfortunately most patients present with late disease that requires radical treatment with considerable morbidity and mortality. Aim: This study examines factors associated with time of cervical cancer presentation to a tertiary treatment centre in Nigeria. Methodolgy: This is a descriptive study of one hundred and seventy-one patients managed for cervical cancer at the Obstetrics and Gynaecology Department of University College Hospital (UCH), Ibadan, Nigeria. The socio-demographic characteristics, presenting symptoms and number of visits to health care facilities before diagnosis were obtained. The data were analyzed by means of descriptive statistics, t-test and Chi square test. Results: The mean age of the patients was 56.5years. Of the patients, 60.7% had been to another health facility on the average of about 2 to 3 times prior to referral to UCH where final diagnoses were made. The average time interval between onset of symptoms and seeking of healthcare was 6.10 +/- 9.31 months, between seeking healthcare and referral to a UCH for eventual diagnosis was 9.35 +/-12.9 months. While 36.3% of the patients presented in early stages of I - Ha, 63.7% presented in late stages of lib - IV. Conclusions: Patients' delay in seeking healthcare and care providers' delay in ensuring proper final diagnosis are associated with late presentation in this study. Preventive and promotive health education to ensure early presentation, prompt and appropriate referral system, early and accurate diagnosis, when ensured, will reduce cervical cancer-related morbidity and mortality